Moderating effects of similarity on the relationship between CSR efforts and anger felt during a product-harm crisis - Ang, Hiang Ling (2012)
Companies today have branched into Corporate Social Responsibility (CSR) in an attempt to appear ‘responsible’ to consumers but despite much of the documented researches on its benefits, the area of CSR acting as ‘reputation insurance’ in times of product-harm crisis have not been greatly explored. In addition, will this be subjected to changes if there is similarity between the CSR efforts the firm undertakes and the nature of the product-harm crisis?